Exploring the Barriers in the Uptake of the Dutch MRSA 'Search and Destroy' Policy Using the Cascade of Care Approach - Annette C. Westgeest; Emile F. Schippers; Martijn Sijbom; Leo G. Visser; Mark G. J. de Boer; Mattijs E. Numans; Merel M. C. Lambregts; on behalf of the MRSA Network Holland West (MDPI AG, 2022)
The Dutch 'search and destroy' policy consists of screening patients with an increased risk of methicillin-resistant Staphylococcus aureus (MRSA) carriership and subsequent decolonization treatment when carriership is found. Decolonization therapy of individual MRSA carriers is effective. However, the effectiveness of the national 'search and destroy' policy is dependent on the entire cascade of care, including identification, referral, and subsequent treatment initiation in MRSA carriers. The aim of this study was to evaluate the leakages in the cascade of MRSA decolonization care. We assessed familiarity with the 'search and destroy' policy and the barriers in the uptake of MRSA eradication care using a questionnaire among 114 Dutch general practitioners. The main reasons for treatment were planned hospital visits, occupational reasons, and infections. The main reasons for refraining from eradication treatment were unfamiliarity with the 'search and destroy' policy and the assumption that MRSA carriership is often self-limiting. To optimize the continuity of the cascade of care, interventions should be aimed at supporting general practitioners and facilitating treatment and referral.